Chapitre 8. Injustices épistémiques, production et circulation de savoirs inclusifs - Fricker, Miranda; Bujold, Audrey; Vallée-Ouimet, Sandrine (Philosophies et sciences infirmières : contributions essentielles à la discipline, 2024)
Cet ouvrage pédagogique regroupe 18 chapitres écrits par des auteurs en sciences infirmières issus de champs d’expertise variés et des plus pertinents. Chaque chapitre présente les fondements ontologiques et épistémologiques de même que l’articulation des concepts clés de philosophes qui exercent une influence majeure sur les sciences infirmières et la pratique des soins infirmiers à l’aide d’exemples pour la pratique, la recherche et la théorisation dans cette discipline.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; production des savoirs; pédagogie; périodes historiques; québec; régions géographiques; santé; sciences humaines; thématiques; travail; épistémologie

Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Essai français, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»--Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

La nature a-t-elle un genre ? Variétés d’écoféminisme - Larrère, Catherine (Cahiers du Genre, 2015)
L’écoféminisme est un mouvement qui s’est développé surtout dans les pays anglophones et qui, en montrant la liaison entre l’oppression des femmes et la domination de la nature, cherche à les combattre ensemble. Cependant, le féminisme s’est largement construit contre la naturalité du sexe, puis du genre. Écologiser le féminisme, n’est-ce pas l’ouvrir à la naturalisation ? En examinant l’écoféminisme culturel (principalement américain), puis social (plus présent dans le Sud, et liant la domination des femmes et de la nature au colonialisme et à l’impérialisme), nous montrerons comment la réflexion féministe sur la nature tend à mettre en question l’évidence de celle-ci, sans en abandonner la référence.
Keywords: approches et analyses; discipline; environnement; nature; philosophie; projet charge mentale; ressource en ligne; santé; sciences humaines; thématiques; écoféminisme

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Exploration of romantic relationships in adolescent females - Wisnieski, Deborah (The University of Oklahoma, 2009)
Adolescence is a time to explore and develop romantic relationships. Glamorized sexual messages and images bombard youth as they struggle to develop their sexual identity. The darker side of romance that includes teen pregnancy, STDs, and emotional pain is rarely portrayed. Because adolescent females shoulder the burden of unwanted sexual outcomes, an exploration of their experiences, both positive and negative, is the focus of this study. Current literature contains demographic information about who is at risk for unwanted pregnancies and Sexually Transmitted Diseases (STDs), but little is known from the adolescent females’ perspective, about their sexual experiences and even less about normal romantic ideation which drives sexual behavior. This qualitative study utilized ethnographic interviews to explore the experiences of 28 females ages 19-29 from four cultural backgrounds including Euro-American, African-American, American Indian, and Latina. The influence of families, peers, school, and sex education programs was explored for positive and negative experiences. Advice about romantic development to younger adolescent females was sought to gain insight into their development and how to better assist adolescent females in developing healthy romantic relationships. A multi-staged data analysis of the interviews was used to find similarities and differences among the subjects and cross culturally. Discussion of romantic behavior occurred in less than half of the nuclear families. Extended family such as aunts, uncles, and grandparents were named as significant role models by most participants and were frequently described as sources for support and occasionally available for discussion of romantic relationships. Peers were perceived to be sexually active and most behaved in a similar manner. Euro- and African-Americans placed more importance on peer groups. Reproduction was most frequently learned in the school system, rather than from family and peers. The programs were reported as woefully lacking in comprehensiveness. This study calls for policymakers to fund sex education programs for adolescents with potential participation from parents, extended family, and peers. The curriculum should address age-appropriate strategies for discussing romantic and sexual behavior. Additionally, guidelines for monitoring activities and use of new technologies that pose higher risks in early adolescence are most important. Health educators and healthcare providers can utilize these strategies when working with adolescents, families, and peers to improve their romantic relationships and decrease teen pregnancies and STDs.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; amériques; discipline; mémoires/thèses; philosophie; périodes historiques; relations amoureuses; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexualité; thématiques; états-unis; étude qualitative

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Dictionnaire critique du féminisme - Hirata, Helena (Politique d'aujourd'hui, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail